Figuring volatility - Ackbar Abbas (Finance and Society, 2023)
This article argues that there are parallels between developments in modern science and in art and culture, including the culture of finance, and that these developments can be tracked by a notion of volatility not just as change, but as how change itself has changed . Describing this paradigm shift requires a language that is precise but indeterminate, a language akin to metaphor, understood as figures of volatility . Three such figures are anamorphosis, anachronism, and catachresis. These figures are major instantiations of volatility, though they do not exhaust all the possibilities. What they indicate is not just that our frames of understanding have shifted, but that we are dealing with problematic, multiple, and overlapping frames: anamorphosis problematizes our experience of space, anachronism of time, and catachresis of language. These figures are not all in play at the same time. In literature, catachresis may be the dominant figure; in dance, anamorphosis; in 'slow cinema', anachronism. The aim is less to arrive at a set of defining characteristics than to follow a series of transformations across different cultural fields. Almost every field in our time is volatile each in its own way, and this has consequences for methodology. If figures are tools to think with, not to regulate thought, a necessary method would be to allow these figures to emerge from the material, not from a checklist. The question of volatility is arguably the key intellectual challenge of our time because it allows us to see deviation from a norm not just as an aberration, but as an indication that established norms are losing their normative value.
Keywords: 300; Overlapping paradigms; painting; precise illegibility; quantum image; slow cinema; Volatility